Numerical investigationof clocking effect of impellerson a multistage pump. Issue 5 (10th June 2019) - Tan, Minggao; Lian, Yichao; Wu, Xianfang; Liu, Houlin
Abstract : Purpose: The purpose of this paper is to investigate the clocking effect of impellers and the superposition between pump stages caused by clocking effect in a five-stage centrifugal pump. Then the best clocking scheme in terms of vibration is tried to be provided as well. Design/methodology/approach: All curves of pressure fluctuation in different impeller stages can be divided into two groups for the difference of 1/16 T in time domain. The difference is mostly in vibration frequency and amplitude, little in pump head and efficiency. Findings: All curves of pressure fluctuation in different impeller stages can be divided into two groups for the difference of 1/16 T in time domain. The difference is mostly in vibration frequency and amplitude, little in pump head and efficiency. Research limitations/implications: This research involves eight different impeller clocking schemes. The results show that the clocking effect has little influence in pump head and efficiency, but the influence in pressure fluctuation is larger. Practical implications: The paper provides guidance for the design of multistage pump for better vibration performance. Originality/value: This research involves eight different impeller clocking schemes, the results show that the clocking effect has little influence in pump head and efficiency, but the influence in pressure fluctuation is larger. Then the best clocking scheme In terms of vibration is tried to be provided through analysis.